The philosophical foundations of Islamic management - Fontaine, Rodrigue Ancelot Harvey (IIUM Press, 2018)
This study seeks to explain the philosophical foundations of Islamic management. Most of the schools of management can be traced back to philosophical ideas. Using the deconstruction approach proposed by Malik (2017), the history of Western philosophy starting with the ancient Greek sis reviewed. At each stage, the similarities and differences between Western philosophy and the teachings of Islam are summarised. The ideas of Adam Smith, Karl Marx and Karl Popper are given special attention. Some of the differences are very significant, especially when it comes to the sources of knowledge and key beliefs. Nonetheless, the philosophies of Adam Smith (in their original form) and Karl Popper are critical. This study concludes that Islamic management seeks to combine the best ideas of Islamic sciences and conventional management while minimizing the negative unintended consequences of conventional management.